Dialogue of knowledge: indigenous justice in Cauca and ordinary justice, a possible cultural exchange - Alvarez Soler, Jaime Antonio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
In my doctoral research work, entitled "Phenomenology of medical education at the Universidad del Cauca", the absence of a relationship between the indigenous communities and the Medicine Program of this university was found. This fact motivated the creation of a research-action project with the indigenous peoples of the department of Cauca. In the application of an ancestral system of "own justice" exercised - without the direct intervention of the State - by the indigenous peoples of Cauca, their authorities have detected situations of inadequate judgments, often unfair, and with serious evidentiary gaps within the processes. Bearing this reality in mind, the base text of this paper proposed the following questions: How is the "own justice system" applied by the indigenous peoples of Cauca ?, and what participatory pedagogical strategies allow for the interaction and recreation of knowledge among indigenous peoples, the Instituto Nacional de Medicina Legal y Ciencias Forenses (National Legal Medicine Institute) and the Universidad del Cauca, as part of the intercultural construct for the protection of the human rights of all people? In this way, an objective was set to make academic sense of the questions posed: to construct, together with the three parties involved, a curricular design to train the indigenous guard and other official support authorities in forensic procedures and dissection of corpses. The pedagogical process and the intercultural practices allowed the exchange of knowledge, but in particular, an approach to the understanding and cosmovison of the "indigenous justice". It was a significant experience that generated new useful concepts to understand the "own justice system" of the indigenous peoples and the negotiated contributions that the Colombian ordinary justice can offer to this ancestral practice.